Automatic Temperature Controlled Fan - Wan Nurulhuda , Selipol Bahari (UTeM, 2008)
Nowadays, the changing of temperature in Malaysia is unpredictable. However,the usage of product such as fan and air conditioner are not enough to solve this problem because of the operation of the product are manually. Because of that, an automatic product of fan is build. The product is an inexpensive and also gives comfortable to the user. The product is operates automatically based on the changing of room temperature. For the detection of room temperature, a temperature sensor is used.The temperature sensor will sends signal to microcontroller and microcontroller will determine to increase or decrease the speed of the fan based on the received signal from temperature sensor.